2014
DOI: 10.1242/jcs.141408
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic K-Ras suppresses IP3-dependent Ca2+ release through remodeling of IP3Rs isoform composition and ER luminal Ca2+ levels in colorectal cancer cell lines

Abstract: BSTRACTThe GTPase Ras is a molecular switch engaged downstream of G-protein-coupled receptors and receptor tyrosine kinases that controls multiple cell-fate-determining signalling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 116 publications
2
58
0
5
Order By: Relevance
“…This may also result in protein degradation. Similarly, in cells expressing mutant K-Ras, decreased IP 3 R3 and SERCA2b protein expression were observed [350], suggesting an overall dampening of the ER-mitochondrial Ca 2+ transfer through oncogenic inhibition that may provide anti-apoptotic benefits to cancer cells. The tumor suppressor p53 was recently shown to initiate cell death in response to cytotoxic agent Adriamycin, ROS and ER stress, by directly interacting with SERCA at MAMs, and activating SERCA to increase ER Ca 2+ uptake [351, 352].…”
Section: Redox Regulation Of Er and Mitochondrial Ca2+ Modulatorsmentioning
confidence: 99%
“…This may also result in protein degradation. Similarly, in cells expressing mutant K-Ras, decreased IP 3 R3 and SERCA2b protein expression were observed [350], suggesting an overall dampening of the ER-mitochondrial Ca 2+ transfer through oncogenic inhibition that may provide anti-apoptotic benefits to cancer cells. The tumor suppressor p53 was recently shown to initiate cell death in response to cytotoxic agent Adriamycin, ROS and ER stress, by directly interacting with SERCA at MAMs, and activating SERCA to increase ER Ca 2+ uptake [351, 352].…”
Section: Redox Regulation Of Er and Mitochondrial Ca2+ Modulatorsmentioning
confidence: 99%
“…In many cases, different mechanisms can be simultaneously operative. For instance, oncogenic KRAS mutations appear to switch the expression from IP 3 R3 into IP 3 R1 and to lower the ER Ca 2+ -store content, together suppressing agonist-induced Ca 2+ release and mitochondrial Ca 2+ accumulation and thus protecting cells against menadione exposure [166]. AKT/PKB phosphorylates all three IP 3 R isoforms, thereby suppressing their pro-apoptotic Ca 2+ -release function [84, 156].…”
Section: The Role Of Ip3r2 In Cell Death and In Senescencementioning
confidence: 99%
“…Moreover, expression levels are directly related to aggressiveness of the tumor [39]. In addition, it has been also reported that depletion of mutated K-Ras in a colon cancer cell line changes Ca 2+ store content and susceptibility to apoptosis by promoting changes in expression of IP 3 R isoforms [40]. Therefore, IP 3 Rs are critical players in Ca 2+ remodeling in colon cancer, contributing likely to changes in Ca 2+ store content and susceptibility to apoptosis.…”
Section: Resultsmentioning
confidence: 99%